New taxa of pygmephoroid mites (Acari: Pygmephoroidea: Pygmephoridae, Neopygmephoridae) phoretic on Enoplotrupes sharpi (Coleoptera: Geotrupidae) from Thailand - Khaustov, Alexander A.; Frolov, Andrey V. (Zootaxa, 2018)
The new species Spatulaphorus enoplotruporum sp. nov. (Acari: Pygmephoridae) and a new monotypic genus and the species Nasutidania orientalis gen., sp. nov. (Acari: Neopygmephoridae) are described phoretic on Enoplotrupes sharpi Rothschild and Jordan (Coleoptera: Geotrupidae) from Thailand. A key to the world species of the genus Spatulaphorus is also provided.